THE INFLUENCE OF SOCIAL MEDIA AND THE SOCIAL ENVIRONMENT ON STUDENT FINANCIAL MANAGEMENT WITH FINANCIAL LITERACY AS A MODERATING VARIABLE (CASE STUDY OF ACCOUNTING STUDENTS OF THE CLASS OF 2024) - Kurnia, Lely; Usman, Ernawaty; Din, Muhammad; Sugianto, Sugianto (Jurnal Manajemen Terapan dan Keuangan, 2026)
Abstract This research investigates how social media exposure and the surrounding social environment shape financial management practices among university students, examining whether financial literacy serves as a moderating factor. Utilizing a quantitative design, the study gathered data via questionnaires from a sample of 127 students. Data were processed using multiple linear regression and Moderated Regression Analysis (MRA) within IBM SPSS. Findings reveal that both social media usage and financial literacy exert a positive and statistically significant impact on students' financial management. In contrast, the social environment demonstrated significance only in the initial model. When analyzed simultaneously, all three variables showed a significant collective influence on financial management outcomes. However, the moderation analysis indicated that financial literacy does not buffer or alter the relationship between social media/social environment and financial management. Consequently, this suggests that financial literacy functions primarily as an independent driver of financial behavior rather than as a moderating variable in this context.  Keywords: social media, social environment, financial literacy, college students' financial management, moderation.